Change of regulating ecosystem services in the Danube floodplain over the past 150 years induced by land use change and human infrastructure - Stammel, Barbara; Amtmann, Mira; Gelhaus, Marion; Cyffka, Bernd (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
Ecosystem services in floodplains are manifold. The regulating services regarding hydrological issues (e.g. flood protection, water purification) are of particular importance along rivers, and depend strongly on size and land use of the floodplain. In this paper, we transfer the commonly known land use changes in floodplains over the last 150 years into significant changes of the amount of different regulating ecosystem services. We investigated a floodplain stretch of 17 km along the Danube in Germany (approx. 90 km²). Thus, we mapped the spatial expansion of the active floodplain and the land use distribution for three different times: the earliest (not the pristine) state of 1869 on the basis of a historical map, 1963 after river regulation and 2013 as navigation channel with a hydropower dam on the basis of aerial photographs. The land use types woodland, grassland, arable land, settlements, and water bodies were distinguished. On the basis of land use as a proxy, we calculated the potential of four ecosystem services (flood retention, nitrogen and phosphorous retention, habitat provision) according to the method of Scholz et al. (2012a). The spatial extension of the active floodplain was continuously reduced from 56 km² (1869) to 18 km² (1963) to 11 km² (2013). The amount of grassland and arable land was reduced significantly in the active floodplain, whereas woodland increased. This entails a decrease of f lood retention (-80%), and nutrient retention (nitrogen: -60%, phosphor: -76%). Likewise, habitat provision was significantly reduced. In total, the potential benefits for humans have been negatively affected over the time by land use change and, above all, by the construction of embankments. Therefore, ecosystem services should be regarded by future floodplain management.